Biotoopia : Bioloogia - Technoloogia - Utoopia. - Helme, Sirje; Tallinn Art Hall, Tallinn; Gallerii Vaal, Tallinn; Galerii Sammas, Tallinn; City Gallery, Tallinn; Ajaloo Instituudi Galerii, Tallinn (Tallinn : Soros Center for Contemporary Arts, 1996)
Annus, Siim-Tanel ; Jaanisoo, Jaan ; Kaljo, Kai ; Keskküla, Ando ; Kruusamäe, Ilmar ; Kurvitz, Raoul ; Kuusing, Kai ; Kõresaar, Andrus ; Laimre, Marko ; Laurits, Peeter Maria ; Lengvinaite, Barbora ; Liiv, Elo ; Mälk, Kadri ; Mähar, Taso ; Mikelsaar, Raik-Hiio ; Neoeksprepost ; Ojaver, Jüri ; Ojaver, Terje ; Punab, Margus ; Remme, Rauno ; Rani, Piret ; Saks, Jaak ; Saks, Reti ; Salupere, Andrus ; Semper, Ene-Liis ; Siib, Liina ; Smidt, Tõnu ; Tammetalu, Tiina ; Tommi & Laurentsius ; Tralla, Mare ; Viljus, Mart ; Vilu, Raivo ; Vint, Toomas
biog., ind. tent., gr. tent., bibliog. [32 p.]
Engels & Ests
Biotoopia : Biology, Technology, Utopia : 3rd Annual Exhibition of the Soros Center for Contemporary Arts, Estonia, Tallinn, November 22 - December 17, 1995, Tallinn Art Hall, Tallinn ; Gallery of the Tallinn Art Hall, Tallinn ; Gallerii Vaal, Tallinn ; Galerii Sammas, Tallinn ; City Gallery, Tallinn ; Ajaloo Instituudi Galerii, Tallinn ; Dominican Monastery
kunstcatalogus